A new species of Leydigia Kurz, 1875 (Cladocera: Chydoridae) from Colombia - Kotov, Alexey A.; Fuentes-Reinés, Juan Manuel (Zootaxa, 2014)
A new species of Leydigia Kurz, 1875 (Cladocera: Chydoridae) is described based on the material from Ciénaga Grande de Santa Marta, Magdalena Department, Colombia. L. lourdesae sp. nov. is a member of the subgenus Leydigia (Neoleydigia) Kotov, 2009, having all diagnostic characters of the latter. It could be the closest relative to L. iberica Kotov & Alonso, 2010, having five setae on exopodite III, a unique for the genus character. But new taxon differs from the latter in a series of characters of the head pores, armature of valve ventral margin, postabdomen, antenna I and II, and limbs I–III. We believe that the basal taxa of L. (Neoleydigia) (including L. lourdesae sp. nov.) are remains of an antique pan-continental group, probably of Mesozoic age, partly survived after the mass extinction and represented now by a series of locally distributed taxa in very distant localities of the planet.